Improving Concentration of Healthy Fatty Acids in Milk, Cheese and Yogurt by Adding a Blend of Soybean and Fish Oils to the Ration of Confined Dairy Cows - Gagliostro, Gerardo Antonio (2020)
Compared to pasture based sistems, milk produced in confined dairy systems is characterized by a high saturated fat (SF) content with a lower concentration of healthy fatty acids (FA) such as vaccenic (VA, trans 11C18:1), conjugated linoleic cid ( cis 9, trans 11 C18:2, CLA), α -linolenic ( cis 9, cis 12, cis -15C18: 3), eicosapentaenoic (EPA, C20:5) and docosahexaenoic (DHA, C22:6) whose presence in milk and dairy products can be increased by feeding polyunsaturated FA (PUFA). The aim of the study was to determine the differences in milk composition and FA profile between a regular (Reg) milk (Reg-Milk), a Reg-Dambo type cheese (Reg-DCh) and a Reg yogurt (Reg-Yog) with that obtained after including a blend (7:1) of soybean (SO) and fish (FO) oils in the total mixed ration (TMR) of lactating dairy cows. The experiment was carried out at the Talar Farm located at Laguna del Sauce, Maldonado Department, Punta del Este, Uruguay Republic during a period of 30 experimental days using a single production batch of 29 Holstein cows. Within this batch, one group of 8 cows (1.88 ± 0.99 calves) in early lactation (135 ± 19 days postpartum) was selected to individually measure milk yield and composition. During the first 7 days of the experiment, cows were fed a TMR without oil-blend inclusion to obtain the Reg-Milk, Reg-DCh and Reg-Yog. From the 8th day onwards, the oil blend was added to the TMR at 4% DM (1.0 kg oil blend cow−1 day−1) and after 23 days of feeding, the modified milk (Mod-Milk) was analyzed and collected to elaborate the modified Dambo-type cheese (Mod-DCh) and Mod-yogurt (Mod-Yog). Milk yield was recorded daily in the selected 8 cows and milk composition was determined over two consecutive days prior to the start of blend-oil supply (Reg-Milk) and at the end of oil supplementation (Mod-Milk) on days 29th and 30th. Milk-tank samples of Reg-Mi and Mod-Mi were also collected and analyzed for chemical composition and milk FA profile. Cheese and yogurt were assayed for its FA profile. Differences in milk yield and composition and in the FA profile before and after oil-feeding were stated using the Student T-test for paired observations. Milk production (kg∙cow−1∙day−1) slightly (−6.7%) decreased ( P < 0.03) from 36.89 (before) to 34.69 after oil feeding. Milk fat content decreased ( P < 0.05) from 3.28 to 3.02 g 100 g−1 g leading to a lower ( P < 0.02) yield (kg∙cow−1∙day−1) of fat corrected milk (4%FCM) from 32.83 (before) to 29.63 after oil. Milk protein content (g 100 g−1) increased ( P < 0.04) from 2.89 (before) to 3.08 (after) oil feeding (+5.92%) a result confirmed ( P < 0.01) in samples taken from the tank. Milk protein output (1.07 kg∙cow−1∙day−1) ( P < 0.96), lactose ( P < 0.65) and total solid ( P < 0.38) contents were not affected. Concentration of non-fat solids (NFS) tended ( P < 0.08) to increase from 8.50 in Reg-Mi, to 8.68 g 100 g−1 in Mod-Mi as it was observed ( P < 0.001) in samples taken from the tank (8.78 vs. 9.93 g 100 g−1). Yield of NFS tended ( P < 0.07) to decrease from 3.14 to 3.01 kg∙cow−1∙day−1 after oil supply. Content of atherogenic FA (C12:0 to C16:0) was significantly ( P < 0.064) reduced (−10.29%) from 44.50 (Reg-Mi) to 39.92 g 100 g−1 (Mod-Mi) with a concomitant decrease ( P < 0.10) in the atherogenic index (AI) from 2.45 (Reg-Mi) to 2.03 (Mod-Mi). Concentration (g 100 g−1 FA) of elaidic ( trans 9 C18:1) and trans 10 C18:1 FA was low in Reg-Mi (0.22 and 0.34 respectively) but tended ( P < 0.11) to increase in Mod-Mi (0.43 and 0.95). Concentration (g 100 g−1 FA) of VA resulted higher (+110%, P < 0.039) in Mod-Mi (2.42) compared to Reg-Mi (1.15). Total CLA content (g 100 g−1 FA) increased ( P < 0.036) from 0.66 in Reg-Mi to 1.36 in Mod-Mi (+106%). Levels (g 100 g−1) of α -linolenic were higher ( P < 0.004) in Reg-Mi (0.34) compared to Mod-Mi (0.29). The omega-6/omega-3 ratio was not changed ( P < 0.13) averaging 5.98 in R-Mi and 7.18 in M-Mi. Oleic acid ( cis 9 C18:1) content (g 100 g−1) remained unchanged ( P < 0.504) averaging 21.99 in Reg-Mi and 22.86 in Mod-Mi. Composition of FA of the Mod-DCh was highly correlated (R2 = 0.999) with FA profile from its original Mod-Mi. A serving of the M-DCh (30 g) theoretically involved a 12.1% reduction in total fat consumption with 16.9% less in SF intake compared to the Reg-Ch. A serving of the M-DCh could putatively increase total CLA consumption by 72.7% compared to the Reg-DCh. Compared to Reg-Yo, a portion (178 g) of the Mod-Yo could increase (69.4%) total CLA intake. The nutritional value of milk fat was improved by feeding a blend of PUFA oils to confined dairy cows and the consumption of the mofified dairy products obtained could promote a lower intake of the potentially atherogenic saturated FA and some increase in healthy FA ingestion.